ChemInform Abstract: Ultrafast Mechanochemical Synthesis of Copper Sulfides. Issue 48 (10th November 2016) - Balaz, Matej; Zorkovska, Anna; Urakaev, Farit; Balaz, Peter; Briancin, Jaroslav; Bujnakova, Zdenka; Achimovicova, Marcela; Gock, Eberhard
Abstract: Covellite, CuS and chalcocite, Cu2 S are prepared within a few seconds by ball milling of the elemental precursors.